Developing critical thinking in student seafarers: An exploratory study (Journal of Applied Learning and Teaching, 2020)
Short course curricula for seafarers using a traditional, teacher-focused, instructional pedagogy has resulted in students demonstrating surface level achievement of learning outcomes and limited development of their critical thinking skills. This paper reports on the introduction of a student-centric pedagogy aiming to develop self-directed learning and critical thinking. The elements included introducing authentic and collaborative learning activities, constructively aligned with the content delivery and assessment. The differences between the current ‘traditional’ approach and a ‘student-centric’ approach was evaluated. This included a pre- and post-test on student assessment, and a set of semi-structured interviews with the students. A thematic analysis identified three themes including: authentic learning, constructivist learning and self-directed learning. The evaluation demonstrated that a student-centric approach promotes critical thinking and active learning in students, improving learning outcomes.